Low-cost nitrogen dioxide monitoring station based on metal oxide sensor and cellular network - Rady Purbakawaca; Arief Sabdo Yuwono; Husin Alatas; I Dewa Made Subrata (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Air pollution has a negative impact on the environment and human health. Meanwhile, the number of conventional air quality monitoring stations is minimal due to high procurement and operational costs. This study proposes a nitrogen dioxide (NO2) pollutant measurement system using the metal oxide sensor (MOX) sensor and cellular network for data transmission in the measurement area. A calibration curve is used to measure NO2 levels based on the sensor's internal resistance changes. Measurement data of NO2 concentration, air temperature, relative humidity, and geospatial information are compiled and sent via global positioning system (GSM), general packet radio service (GPRS) radio communication with transmission intervals of every minute. The database server processes the data and displays it on the web application. System testing results at the Tugu Kujang Bogor at 15:38:00-16:38:00 September 23, 2021, showed that the concentration of NO2 ranged from 0.16-0.52ppm with an average of 270 ppb with an AQI of 133 in the unhealthy category for the sensitive group. The measured NO2 levels are outside the range of the NO2 concentration database in the industrial areas of Bogor and Jakarta for the 2016-2020 period. Therefore, this system provides an excellent opportunity to obtain real-time measurement data in the field.